FXN GAA repeat expansions in amyotrophic lateral sclerosis - Rizik, Naji; Freischmidt, Axel; Ludolph, Albert C.; Weishaupt, Jochen H. (Journal of clinical neuroscience, 2014)
Homozygous trinucleotide expansions in the frataxin (FXN) gene are responsible for Friedreich’s ataxia. However, heterozygous trinucleotide expansion in FXN results in a decreased expression of frataxin, a component of the mitochondrial respiratory chain, and is associated with a subclinical metabolic phenotype. In this study we thus investigated whether heterozygous FXN trinucleotide expansion is a risk factor or modifier for amyotrophic lateral sclerosis (ALS). Genomic DNA from familial and sporadic ALS patients and control individuals was tested for extended FXN trinucleotide repeats by polymerase chain reaction analysis. Screening of 652 ALS patients and 238 controls revealed a lower overall frequency of heterozygously extended FXN repeats than expected. A significant difference in the frequency of the FXN expansion or an associated modification of the disease phenotype in ALS was not detected. Our findings strengthen the view that different DNA repeat expansions are toxic on the basis of specific biological mechanisms.
Gesehen am 29.07.2021